Railway auxiliary power supply system: A modular multilevel converter approach - Rodrigues, Nuno (2022)
When it comes to power railway systems, two main aspects must be considered: (i) the power of the propulsion of the train, which is responsible for the movement of the train; (ii) the power of the auxiliary services, which is responsible for the power inside the train for commodity and service of the passengers. As such, two different converters are used, namely the propulsion converter and the static converter, respectively. This paper proposes a new topology of a static converter, using a modular multilevel converter with high frequency output, with a high frequency transformer to reduce the size of the converter. The output of the converter is responsible for creating a stable singlephase voltage, with nominal values of 230 V - 50 Hz, from a highly variant input voltage available on the DC-link.